TEACHING CHEMICAL PROBLEM SOLVING AND CLASSIFICATION AS A PEDAGOGICAL PROBLEM - Ajiniyazova Sholpan Saparniyazovna (Web of Journals Publishing, 2025)
This article describes the problems that arise when solving chemistry problems in general secondary schools.
Keywords: Problem, educational issue, chemical thinking, mental activity.